Prototype Portable Solar Concentrated Thermoelectric Generator Charging System - Rizki Achmad Baihaqi; Mahendra Widyantono; Aditya Chandra Hermawan; Ayusta Lukita Wardani (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The rapid advancement of technology has led to an increasing demand for electrical energy. One of the efforts to meet this demand is the development of micro-capacity power generation systems utilizing heat energy. Heat energy can be harnessed using thermoelectric elements. This study aims to design and develop a portable power generation system that utilizes solar heat as an energy source. The prototype uses six TEC 1-12706 thermoelectric modules to generate electricity designed specifically to recharge devices such as phones, power banks, and flashlights. Solar heat is concentrated on the thermoelectric modules using Fresnel lenses, while heatsinks are employed for cooling. The thermoelectric modules are connected in series to produce sufficient voltage, which is then boosted by a boost converter. The generated electrical energy is stored in a battery to ensure voltage stability despite temperature fluctuations. This device can also operate at night due to the energy stored in the battery. Test results show that the average output voltage without load ranges from 9.49V to 9.56V, with an average temperature of 45.2°C at the thermoelectric modules. In load tests, the device successfully charged a Pixel 5 phone (5000 mAh battery) from 4% to 70% in 95 minutes. These results demonstrate the potential of this system as a reliable and environmentally friendly portable energy solution.